GRB 050223: a dark GRB in a dusty starburst galaxy - Pellizza González, Leonardo Javier (2006)
Aims.We aim at detecting and determining the properties of the host galaxy of the dark GRB 050223. Methods.We use VLT optical/NIR images coupled to Swift X-ray positioning, and optical spectra of the host galaxy to measure its properties. Results.We find a single galaxy within the Swift error box of GRB 050223. It is located at and its luminosity is L*. Emission lines in the galaxy spectrum imply an intrinsic yr-1, and a large extinction mag within it. We also detect absorption lines, which reveal an underlying stellar population with an age between 40 Myr and 1.5 Gyr. Conclusions.The identification of a host galaxy with atypical properties using only the X-ray transient suggests that a bias may be present in the former sample of host galaxies. Dust obscuration together with intrinsic faintness are the most probable causes for the darkness of this burst.